Crazy, weak, and incompetent: a directed content analysis of self-injury stigma experiences - Staniland, Lexy (Deviant behavior, 2023)
Despite significant impacts to mental health and support-seeking, non-suicidal self-injury (NSSI) stigma remains under-studied and poorly understood. Recently, the NSSI Stigma Framework was proposed, conceptualizing NSSI stigma as comprising six constructs (origin, concealability, course, peril, aesthetics, disruptiveness) that manifest across four perspectives (public, self, anticipated, enacted). The present study investigated the extent to which this framework can account for individuals’ NSSI stigma experiences using a directed content analysis. Written responses from 99 university undergraduates (Mage = 21.5, SD = 3.7; 83.8% female) generated 731 data units for analysis, of which 299 (40.9%) were coded. Results demonstrated support for the public and enacted perspectives, with participants describing stigma experiences within friendships, families, schools, and workplaces. Data pointed to both direct and indirect experiences of public stigma, suggesting a more nuanced understanding of this perspective is required. While there was sufficient support for a majority of elements, more work is needed to verify the applicability of the self and anticipated perspectives. Our findings contribute to a growing body of research investigating NSSI stigma, and provide preliminary support for the utility of the NSSI Stigma Framework in identifying multiple facets of NSSI stigma. Implications for intervention and future research are discussed.